Iron and nitrogen co-doped graphene quantum dots as highly active peroxidases for the sensitive detection of l-cysteine. (4th October 2021) - Deng, Xiaochun; Zhao, Jingwen; Ding, Yao; Tang, Hongliang; Xi, Fengna
Abstract : New Fe, N co-doped GQDs are easily synthesized and have high peroxidase-mimicking activity for the selective and sensitive colorimetric detection of l -cysteine. Abstract : As an alternative to natural enzymes, peroxidase nanozymes have shown great potential in the fields of sensing, drug delivery, and tumor treatment. However, obtaining peroxidase nanozymes with high catalytic activity, simple synthesis, and low cost is still a huge challenge. Herein, we demonstrate facile synthesis of iron and nitrogen co-doped graphene quantum dots (Fe, N-GQDs), which possess high peroxidase activity. With hemin being a precursor, Fe, N-GQDs can be easily synthesized with a high production yield (74%) using a one-step hydrothermal process. The as-prepared Fe, N-GQDs exhibit uniform size (2.9 nm), good water dispersibility and bright yellow-green fluorescence (an absolute fluorescence quantum yield of 12.5%). In particular, Fe, N-GQDs exhibit very high peroxidase-mimicking activity and can rapidly oxidize peroxidase substrates 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to produce blue oxidized TMB (oxTMB) in the presence of H2 O2 . In comparison with a natural enzyme horseradish peroxidase (HRP), the Fe, N-GQD nanozyme has a lower Michaelis constant ( K m ) and a higher maximum reaction rate ( V max ), indicating higher substrate affinity and faster reaction rate. Selective and sensitive colorimetric detection of l -cysteine (l -Cys) is realized in terms of its ability to reduce oxTMB and to react with H2 O2 . The linear range for the detection is 0.5–50 μM with a limit of detection (LOD) of 140 nM. In addition, the detection of l -Cys in compound amino acid tablets is also realized.